2012
DOI: 10.1039/c2mt20092a
|View full text |Cite
|
Sign up to set email alerts
|

Detection of metals and metalloproteins in the plasma of stroke patients by mass spectrometry methods

Abstract: Stroke is the leading cause of disability in adults world-wide. Well-recognized environmental risk factors for stroke include hypertension, smoking, diabetes mellitus, atrial fibrillation and atherosclerosis. Ischemic stroke, which accounts for ~85% of all stroke, is mainly caused by either intracranial thrombosis or extracranial embolism; hemorrhagic stroke can be classified as either intracerebral hemorrhage (ICH) or subarachnoid hemorrhage (SAH). Metalloproteins and metals play key roles in epigenetic event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 101 publications
0
13
0
Order By: Relevance
“…As previously mentioned, studies with human patients have suggested an imbalance in copper homeostasis after cerebral ischemia [11,12]. Elevated levels of copper were observed in the circulation of stroke patients in both studies, suggesting that copper is redistributed due to stroke-induced damage.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…As previously mentioned, studies with human patients have suggested an imbalance in copper homeostasis after cerebral ischemia [11,12]. Elevated levels of copper were observed in the circulation of stroke patients in both studies, suggesting that copper is redistributed due to stroke-induced damage.…”
Section: Discussionmentioning
confidence: 52%
“…While copper homeostasis is disturbed in chronic neurodegenerative diseases such as Alzheimer's disease (AD) [10], little is known about copper homeostasis in acute ischemic stroke. Several years ago, Kodali et al reported an increase in the plasma copper concentrations of ischemic stroke patients [11]. This observation was supported by a recent paper demonstrating that serum levels of both total copper and copper loosely bound to small molecules are elevated in serum of ischemic stroke patients [12].…”
Section: Introductionmentioning
confidence: 82%
“…Previous studies have indicated that metal toxicity is involved in stroke etiology [17] . The OR for stroke was not attenuated following adjustment for cobalt (often considered to be the principle toxic agent) and molybdenum.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our prior findings 5 and supportive evidence in the literature, 616 we tested the following 6 potential biomarkers for their potential utility in stroke diagnosis: paraoxonase-1, matrix metalloproteinase (MMP)-3, MMP-9, apolipoprotein (Apo) A-I, Apo C-I, and Apo C-III.…”
Section: Introductionmentioning
confidence: 94%